Carbon footprint of tourism in the Zapanal Waterfalls, Cotopaxi province - Zambrano Fernández, Lisseth Johanna (2026)
The carbon footprint measured the amount of greenhouse gases emitted by tourists at the Zapanal Waterfalls. The research aimed to determine the sources of emissions from tourism-related activities. An identification form, an observation sheet, was used to identify five sources: dining, electricity, transportation, food/beverages, and common waste. A quantitative survey was randomly administered to tourists on weekends from October 21 to November 11, 2023, yielding a total of 440 respondents. The three emission categories identified in kilograms of carbon dioxide equivalent were: Scope 1, directly, with an emission of 112.2 kgCO2-eq from gas consumption in the dining area; Scope 2, indirectly, with 0.0022 kgCO2-eq from the use of a connected cell phone charger; Scope 3, indirectly, with car use by tourists, 346.5 kgCO2-eq; consumption of pork and bottled water emitted 142.88 kgCO2-eq; and common waste such as plastics, paper, cardboard, and food scraps, 333.58 kgCO2-eq. The results showed a total carbon footprint of 935.16 kgCO2-eq for the Zapanal Waterfalls, and 3.10 kgCO2-eq for tourists. The environmental management plan was based on ISO 14001, assessing environmental aspects and designing five programs: environmental contingency, efficient energy use and conservation, emissions mitigation and adaptation, comprehensive management of common waste, and water resource protection.